An Insight Into Ancient Aeolian Processes and Post‐Noachian Aqueous Alteration in Gale Crater, Mars, Using ChemCam Geochemical Data From the Greenheugh Capping Unit. Issue 9 (19th September 2022) - Bedford, Candice C.; Banham, Steven G.; Bridges, John C.; Forni, Olivier; Cousin, Agnes; Bowden, Donald; Turner, Stuart M. R.; Wiens, Roger C.; Gasda, Patrick J.; Frydenvang, Jens; Gasnault, Olivier; Rammelkamp, Kristin; et al.
Abstract: Aeolian processes have shaped and contributed to the geological record in Gale crater, Mars, long after the fluviolacustrine system existed ∼3 Ga ago. Understanding these aeolian deposits, particularly those which have been lithified and show evidence for aqueous alteration, can help to constrain the environment at their time of deposition and the role of liquid water later in Mars' history. The NASA Curiosity rover investigated a prominent outcrop of aeolian sandstone within the Stimson formation at the Greenheugh pediment as part of its investigation of the Glen Torridon area. In this study, we use geochemical data from ChemCam to constrain the effects of aeolian sedimentary processes, sediment provenance, and diagenesis of the sandstone at the Greenheugh pediment, comparing the Greenheugh data to the results from previous Stimson localities situated 2.5 km north and >200 m lower in elevation. Our results, supported by mineralogical data from CheMin, show that the Stimson formation at the Greenheugh pediment was predominately sourced from an olivine‐rich unit that may be present farther up the slopes of Gale crater's central mound. Our results also suggest that the Greenheugh pediment Stimson formation was cemented by surface water runoff such as that which may have formed Gediz Vallis. The lack of alteration features in the Stimson formation at the Greenheugh pediment relative to those of the Emerson and Naukluft plateaus suggests that groundwater was not as available at this locality compared to the others. However, all sites share diagenesis at the unconformity. Plain Language Summary: We use geochemical data from the Curiosity rover's ChemCam instrument to investigate the geological history of the Greenheugh pediment capping unit. The Greenheugh pediment is a geologic feature that has a gently sloping top, forming a broad plain extending from the base of the valley, Gediz Vallis. The Greenheugh pediment is capped by a unit of broadly uniform thickness which represents the remains of the Stimson dune field that existed <2.5 Ga (mid‐to late‐Hesperian). ChemCam geochemical data shows that the sands deposited at the Greenheugh capping unit were largely sourced from a nearby olivine‐rich unit. Surface waters then cemented the windblown sand deposits, ponding at the unconformity with the underlying mudstone unit, creating concretions toward the base. Episodes of groundwater circulation did not affect the rocks at Greenheugh as much as they did at other Stimson localities, though both sites share evidence of acid‐sulfate alteration along the unconformity. These results suggest that the ancient Stimson dune field was a dynamic environment, incorporating grains from the surrounding geological units on Mt Sharp. Furthermore, liquid water was stable at the surface in the Hesperian and was available for multiple diagenetic events along bedrock weaknesses. Key Points: ChemCam geochemical results support that the Greenheugh pediment capping unit was deposited within the Stimson sand sea in the Hesperian The Greenheugh pediment capping unit was sourced from olivine‐rich sands, potentially recycled from units farther up Mt Sharp Greenheugh experienced less interaction with groundwaters than Stimson at the Emerson and Naukluft plateaus, but shared diagenesis at the unconformity